Natural Factors on Heterogenetic Accumulations of PTEs in Sloping Farmland in a Typical Small Mountainous Watershed in Southwest China - Ya Gao; Bihan Gu; Lingchen Mao; Daofang Zhang; Hong Tao (Separations, 2022)
High potential toxic element (PTE) concentrations in soils that exceed local regulatory threshold values have been reported in non-polluted mountainous areas worldwide. However, there have been few studies that have comprehensively investigated the contribution of natural factors including the parental material, pedogenesis processes and physiochemical properties of soils on the distribution of PTEs in these soils. Therefore, in this study, we studied the distribution of 13 PTEs in sloping farmland soils collected from a mountainous watershed in Guizhou Province, Southwest China. The contributions of natural influencing factors were analyzed using a geostatistical analysis and a geographic detector method. All of the PTEs were unevenly distributed, especially Sb, and the average contents of V, Cr, Co, Ni, Cu, Zn, As, Mo, Cd, Sb, Tl, Pb and Hg were 57.15, 36.20, 4.61, 12.61, 13.36, 63.50, 11.94, 0.78, 0.37, 6.44, 0.48, 27.42 and 0.36mg/kg, respectively. The proportion of samples with Cd, Hg and As exceeding the screening value of the soil pollution risk of agricultural land in China was 46.7%, 5.9% and 4.4%, respectively. Except for Cd and Pb, the q values of the PTEs calculated from the geographical detector were above 0.05, indicating that altitude changes, which affect the pedogenesis process, have a great impact on the spatial distribution. Stratigraphic factors contributed greatly to the distribution of Co, Ni and Cu, which indicates their similarity in parental material. The combined effect of clay content, topographic factors and agricultural land types had the strongest explanatory power for V, Cr, Mo and Pb. The distributions of As, Sb, Tl and Hg are strongly associated with a potential source of mercury ore, and their accumulation is also enhanced by the adsorption on soil clay. Agricultural As also contributes to its distribution.